Nitrate Assimilatiun in Leaf Blades of Eucalyptus - Pokhriyal, T.; Raturi, A. S. (Indian Forester, 1984)
The method for assay of in vivo nitrate roduclase (NR) activity was standardised for for Eucalypllls leaf blades. The maximum activlly (m moles NO3- reduced g dr wt-1 H-1 was obtained with a 0.1 m phosphate buffer of pH 7.5 and 0.025 potassium nitrate concentration. Among the ten Individual lear blades (in descending order from the tip) maximum NR activity (m moles NO-3 reduced g dry wt-1 H-1) was obServed in the young (juvenile) ones, and further it dedreased with the increase in the age. Whereas, the total NR activity per leaf blade was higher in the middle order leaves (4th to 6th) and lowest in the tenth leaf. An increase in the fresh and dry weights of The leaves was observed upto seventh leaf, thereafter it remained almost constant.